Locomotion of commercial broilers and indigenous chickens - Figueiredo Alves, Marilia Carvalho; Lima Almeida Paz, Ibiara Correia de [UNESP]; Naas, Irenilza de Alencar; Garcia, Rodrigo Garofallo; Caldara, Fabiana Ribeiro; Araujo Baldo, Grace Alessandra de [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Molino, Andrea de Britto (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2016)
This study aimed to evaluate the relationship between the steadiness of broilers during the stance phase of locomotion, and the primary disorders of the locomotor system and gait. The experimental design was completely randomized, in a factorial arrangement (2 x 2 + 32), indicating two sexes and two genetic commercial strains, with five replications of 53 broilers each, and 32 (16 males and 16 females) indigenous chickens. Gait score and valgus and varus condition were assessed. Pictures of the birds were taken and evaluated. The broiler body was considered a spherical shape, and the centroid was calculated. From the geometric center of the body, a line was drawn perpendicularly to the sphere radius that formed an angle (ANG) with the other vertical line drawn from the centroid to the ground. The angle projected onto the ground was analyzed, and the body steadiness (EC) was estimated. At the 42nd day of growth, broilers were weighed to assess the body weight, the breast weight after slaughter, and the percentage of the breast (PB). Femoral degeneration, tibial dyschondroplasia, spondylolisthesis, and footpad dermatitis were evaluated. Fast-growing broilers presented a high prevalence of locomotor issues. The PB was not affected by sex or genetic strain. Males showed better ANG than the females, regardless of the genetic strain. More balanced EC was found in commercial broilers when compared with the indigenous chicken that stood slightly towards the back during the stance phase. A medium (in males) to high (in females) association between EC and ANG was found amongst broilers from the commercial strains in both males and females. The broilers from commercial strains presented more locomotor issues than the indigenous chicken. Commercial broiler strains show less locomotor soundness than indigenous chickens.
Keywords: bone pathology; postural balance; welfare